Effects of extraction temperatures on total flavonoid content and antioxidant activity of Piper sarmentosum Roxb. (Kaduk) / Nor Fadilah Rasuli - Rasuli, Nor Fadilah (2015)
Piper sarmentosum Roxb. or "Kaduk", is one of potential herb to treat chronic diseases. It is traditionally consumed as drink and carminative as it contains various bioactive compounds with antioxidant activity. The yield of antioxidant compound from plants is influenced by several parameters including temperature, pH and solvent during nourishment or beverage process preparation. To date, there is no information regarding the effect of heat treatment on antioxidant content and activity of Piper sarmentosum Roxb. leaf. The present study evaluates the effect of different extraction temperatures on the total flavonoid content (TFC) of Piper sarmentosum Roxb. leaf and their corresp~nding antioxidant scavenging activities. Colorimetric aluminium chloride assay were used to measure the TFC of Pir.er sarmentosum Roxb. leaf extracts at temperature 30°C, 40°C, 50°C, 60°C, 70°C, 80 C, 90°C and 100°C. The antioxidant free radical scavenging activity was measured using 2,2-diphenyl-I-picryhydrazyl (DPPH) assay. TFC of Piper sarmentosum Roxb. was significantly elevated with increasing of extraction temperature (p<0.05) starting from 8.54 until 22.6ImgQE. In addition, increase extraction temperature also significantly increase antioxidant free scavenging activity of Piper sarmentosum Roxb from 42.39 until 89.76% compared to unheated Piper sarmentosum Roxb. extract, 24.3%. TFC (0.02mg/ml) content were highly correlated with DPPH free radical scavenging activities (R = 0.866) and is influenced by extraction temperature. In conclusion, extraction temperature significantly influence the antioxidant content and activities as the highest level of TFC and antioxidant scavenging activity observed when P.sarmentosum Roxb leaves heated at 100°C.